Assessment of heavy metal contamination and its mobilization from selected landfills in Selangor / Nur Aliya Hamdi - Nur Aliya , Hamdi (2017)
In this study, the comparison of the total concentration and mobilization of heavy metals (Pb, Zn, Mn, Cu and Ni) in soil from active and closed cells in Jeram Sanitary Landfill as well as the contamination factor and risk of heavy metals in soils were investigated. Soil samples from active and closed cell were dried and homogenized and sequentially extracted. The total heavy metal concentration were determined by pseudo total digestion procedure, while the speciation pattern of heavy metals were done using Tessier’s five steps sequential extraction procedure and further analyzed with ICP-MS. The results obtained from the analysis indicated that the concentration of heavy metals in open cell were higher than that from the closed cell. Level of Pb concentration in the active cell was higher than the closed cell in all samples. In a sequential extraction procedure, it is obvious that Mn was identified in the greatest amounts in mobile phase whereas Cu and Pb showed the greatest amount in immobile phase in soils at all stations. The heavy metal contamination factor was also determined in this study, based on the contamination factor values to indicate the degree of heavy metals risk to the environment. It was found that the soil was possibly polluted with Mn, Zn and Ni. RAC value calculated in this study showed medium risk for active cell and low risk for closed cell for most of the heavy metals except for Mn. Although Pb was found to be the highest concentration in all samples due to its non-mobility state in soil, it is at low risk to the environment.